2001
DOI: 10.1046/j.1523-1755.2001.0590031077.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry proves under-O-glycosylation of glomerular IgA1 in IgA nephropathy

Abstract: The O-glycan side chains in the hinge of the glomerular IgA1 were highly underglycosylated in IgAN. These results indicate that the decreased sialylation and galactosylation of the IgA1 hinge glycopeptides play a crucial role in its glomerular deposition in IgAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
158
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(168 citation statements)
references
References 23 publications
7
158
0
3
Order By: Relevance
“…Recently, analysis of O-glycans in IgA1 from patients with IgAN by fluorophore-assisted carbohydrate electrophoresis revealed an increase in the percentage of O-glycans with single GalNAc with no difference in the percentage of sialylated glycans. Two studies have also demonstrated that the eluted glomerular IgA are underglycosylated [32, 33]. These observations do not necessarily contradict our present finding in which the anionic pIgA1 subfraction from IgAN patients are found to be more sialylated.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, analysis of O-glycans in IgA1 from patients with IgAN by fluorophore-assisted carbohydrate electrophoresis revealed an increase in the percentage of O-glycans with single GalNAc with no difference in the percentage of sialylated glycans. Two studies have also demonstrated that the eluted glomerular IgA are underglycosylated [32, 33]. These observations do not necessarily contradict our present finding in which the anionic pIgA1 subfraction from IgAN patients are found to be more sialylated.…”
Section: Discussionsupporting
confidence: 84%
“…Top-ranked genes have been reported with roles in disease, regulation, signaling, and apoptotic pathways, however formal Partek pathway analysis identified only three pathways with P < 0.05; top-ranked was mucin type O-glycan biosynthesis (P = 0.02) and it is of note that mucin-type O-glycosylation is important for kidney development with abnormalities associated with renal dysfunction, abnormal glomeruli, proximal tubules, and renal podocytes. [39][40][41] Enrichment based on gene ontology also highlighted O-glycosylation with the most significant results being for biological processes protein O-linked glycosylation via serine (P = 0.002, GO ID = 18 242) and protein O-linked glycosylation via threonine (P = 0.002, GO ID = 18 243). Analysis of the interaction profile did not reveal anything of note.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of their increased accessibility to glycosyltransferases, IgA glycans are more likely to be sialylated, which allows IgA clearance to be regulated by ASGP-Rs. In the setting of IgA-mediated nephropathy, alterations in IgA1 glycans have been well documented [30]. Decreased sialylation and galactosylation results in altered IgA1 aggregation and impaired ASGP-R-mediated clearance.…”
Section: A Vast Amount Of Information Is Stored In a Cell’s Glycocalyxmentioning
confidence: 99%